Home ('Griha') - Rokeya Sakhawat Hossain - Quayum, Mohammad Abdul (Flinders University, Australia, 2012)
A translated essay from Bengali to English. The essay was originally published in 1905 by the acclaimed Bengali writer Rokeya Sakhawat Hossain.